2007
DOI: 10.1007/s11060-007-9328-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of co-overexpression of the EGFR/IGFBP-2/HIF-2A genes in astrocytomas

Abstract: Overexpression of the EGFR, IGFBP-2 and HIF-2A genes has been observed in high-grade astrocytomas and these genes seem to be functionally related to one another. This study aimed to define the profile of their expressions, interactions and correlation with clinical features and prognostic significance in microdissected tumor samples from 84 patients with astrocytomas of different grades and from 6 white matter non-neoplasic brain tissue sample. EGFR, IGFBP-2 and HIF-2A gene expression levels were analyzed by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
0
22
0
2
Order By: Relevance
“…22 Previous studies have shown that increased IGFBP-2 expression in a tumor promotes glioma cell migration and invasion through activation of the matrix metalloproteinase 2 protein and integrin pathway [23][24][25][26][27] and that this increased expression is associated with glioma malignancy and poor survival of glioma patients. 12,13,16,18,[28][29][30][31][32][33] Attenuation of IGFBP-2 by the tumor suppressor protein IIp45 or using small interfering RNA resulted in decreased cell motility and invasion. 23,26 Recently, IGFBP-2 has been found to be a "driver" oncogene for glioma development and progression.…”
mentioning
confidence: 99%
“…22 Previous studies have shown that increased IGFBP-2 expression in a tumor promotes glioma cell migration and invasion through activation of the matrix metalloproteinase 2 protein and integrin pathway [23][24][25][26][27] and that this increased expression is associated with glioma malignancy and poor survival of glioma patients. 12,13,16,18,[28][29][30][31][32][33] Attenuation of IGFBP-2 by the tumor suppressor protein IIp45 or using small interfering RNA resulted in decreased cell motility and invasion. 23,26 Recently, IGFBP-2 has been found to be a "driver" oncogene for glioma development and progression.…”
mentioning
confidence: 99%
“…Consistent with this, it has been reported that HIF2α drives tumor progression in renal carcinoma cells in which there is a gradual shift from HIF1α to HIF2α expression with increasing tumor grade [83]. HIF2α (but not HIF1α) has been shown to cooperate with a number of oncoproteins frequently deregulated in cancer such as c-Myc, epidermal growth factor receptor (EGFR), and K-Ras [84][85][86] and has been linked to increased tumor aggressiveness through the promotion of self-renewal and epithelial to mesenchymal transition (EMT). In addition, Koh et al [80] identified the hypoxia-associated factor (HAF) as an E3 ubiquitin ligase that binds to and ubiquitinates HIF1α by an oxygen-and pVHL-independent mechanism, targeting HIF1α for proteasomal degradation.…”
Section: Hifs Promote Stemness and Cancer Aggressivenessmentioning
confidence: 55%
“…The relationship between HIFs level and cancer progression has been investigated in many cancer types, and has even raised the prospect of targeting HIFs as a possible cancer therapy [26]. Specifically, HIF-2α is thought to serve as a crucial factor in glioma cell survival and a prognostic marker in glioma patients [27,38]. Our data reveal that the HIF-2α level in glioma cells is decreased after down-regulation of H-ferritin (Figure 3c).…”
Section: Discussionmentioning
confidence: 70%